PENGGUNAAN MEDIA PEMBELAJARAN DOT CARDS TERHADAP KEMAMPUAN HITUNG PENJUMLAHAN DAN PENGURANGAN PADA ANAK AUTIS DI SDLB - AYU FARADILLAH, YULIA (Jurnal Pendidikan Khusus, 2017)
Abstract Learning mathematics was an important thing in life but learning mathematics also became one of the difficulties experienced by autism children, especially the counting material of adding and subtracting. With the difficulties above we, as the educators, had responsibility to help the children in solving the difficulty experienced, one of them by making learning media which could be understood by the children. The learning media was Dot Cards because it had several advantages on it such as conveying learning material could be uniformed, the learning process was clearer and more interesting, and the learning process was more interactive so the learning media of Dot Cards became the suitable media for learning counting of adding and subtracting to autism children. This research purpose was to find the influence of using learning media of Dot Cards toward adding and subtracting ability to autism children in SDLB Bhakti Wiyata Surabaya. This research used quantitative approach with “One Group Pretest – Posttest Design”. The subject of this research was autism children in SDLB Bhakti Wiyata Surabaya numbering 8 children. To analyze the data used non parametric formula with Sign Test and the methods of data collection used observation and test. From the data analysis it was obtained the counting result of critic value 5% with Z table = 1,96 it was a fact that ZH value = 2,5 was greater than critic value of Z table 5% (1,96) so the null hypothesis (Ho) was refused and work hypothesis (Ha) in this research i.e. “there was influence of using learning media of Dot Cards toward adding and subtracting ability to autism children in SDLB Bhakti Wiyata Surabaya” was accepted. In this way it could be concluded that learning media of Dot Cards influenced toward adding and subtracting ability to autism children in SDLB Bhakti Wiyata Surabaya. Keywords: media Dot Cards, adding and subtracting